55‐1: Invited Paper: Prediction of Overall HDR Quality by using Perceptually Transformed Display Measurements. Issue 1 (May 2017) - Choudhury, Anustup; Farrell, Suzanne; Atkins, Robin; Daly, Scott
Abstract : The need for metrics to evaluate HDR display subjective performance is becoming widely recognized. Yet most existing performance metrics focus on physical measurements rather than subjective impact. We found that applying perceptual transforms to five key HDR performance characteristics better predicts display quality compared to existing physical metrics.